2021
DOI: 10.1108/jfm-04-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

Bank’s battle against insider frauds ignitors and mitigators: an emerging nation experience

Abstract: Purpose Banks are exposed to many challenges to name a few i.e. growing market competition, political environment, market forces of demand and supply, technological changes, frauds and poor management. The banking sector devasted experiences of fraud have impacted all facets of the Banking, Financial Services and Insurance. In continuation, this study aims to revolve around themes of different types of frauds, especially insider frauds that have gained mainstream attention in recent major value fraud events wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In the USA and Nigerian banks, scholars (Okoye and Gbegi, 2013; Ramamoorti, 2008) examined how poor internal control, poor cyber security and poor corporate governance practices affected profitability. Researchers (Roy and Basu, 2021; Uchenna and Agbo, 2013) found that employees exploited loopholes in the infrastructure, technology, database and communication systems to commit crimes in Nigeria and Kenya. Some studies (Çetinkaya and Damar, 2019) found that social and political pressures, easy escape policies, weak internal control systems and inadequate supervision work as pull factors for employees to commit fraud.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA and Nigerian banks, scholars (Okoye and Gbegi, 2013; Ramamoorti, 2008) examined how poor internal control, poor cyber security and poor corporate governance practices affected profitability. Researchers (Roy and Basu, 2021; Uchenna and Agbo, 2013) found that employees exploited loopholes in the infrastructure, technology, database and communication systems to commit crimes in Nigeria and Kenya. Some studies (Çetinkaya and Damar, 2019) found that social and political pressures, easy escape policies, weak internal control systems and inadequate supervision work as pull factors for employees to commit fraud.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In banks, the least secure encryption system serves as an easy target for fraudsters. An inefficient IT control system is another fraud enabler (Roy and Basu, 2021). Poor internal control measures can sometimes result in criminal activities going undetected for 12 months and even five years (Van Akkeren and Buckby, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Banks manage the dynamically rising digital disruptions that prevent emerging nation banks from adhering to standard best practices (International Finance Corporate, 2021). Some of the challenges are stability (Batten et al, 2017), reputation and risk management (Ketterer, 2017;Roy and Basu, 2021a). Cyber-attacks are the most significant challenge among all technological disruptions that affect the banking business (Chhabra and Viswanathan, 2020;Roy and Vishwanathan, 2018;Touri, 2009) around its reputation, sustainability and stability (Thompson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They identified that fraud could happen because of either party involvedthe victim or the criminal. The authors of recent studies (Blass and Grossman, 1996;Eaton and Korach, 2016;Najafabadi et al, 2015;Resnik and Finn, 2018;Roy and Basu, 2021a) believe that investigations should focus on involved parties since both are internal to the fraud and can be easily monitored and controlled (Swaby, 2012). As part of the root-cause analysis, both the victim (bank) and the fraudster (an insider employee in this case) provide reasons for the fraud.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation